REKONSTRUKSI PROSES MEDIASI KELUARGA INDONESIA - Azzuhri Al Bajuri (Hukum Islam, 2020)
Abstract : The gap between the expectations of the application of the PERMA Mediation Procedure in the Court with the increasing number of mediation failures especially in the case of families in Indonesia. This research is a qualitative research using library research method with normative-juridical empirical approach with system theory proposed by Jasser Audah. The results of this study suggest that the reconstruction of the Indonesian family mediation process by establishing new rules is an urgent need to reduce the number of divorces in Indonesia.Abstrak : Kesenjangan antara harapan penerapan PERMA Prosedur Mediasi di Pengadilan dengan jumlah kegagalan mediasi yang semakin meningkat terlebih dalam perkara keluarga di Indonesia. Penelitian ini merupakan penelitian kualitatif dengan metode penelitian pustaka dengan pendekatan normatif-yuridis empiris dengan teori sistem yang dikemukakan oleh Jasser Audah. Hasil dari penelitian ini mengemukakan bahwa rekonstruksi proses mediasi keluarga Indoesia dengan membentuk aturan baru adalah kebutuhan yang sangat mendesak untuk menekan jumlah perceraian di Indonesia.